2008
DOI: 10.1128/aac.01595-07
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Susceptibility Profile of Candida metapsilosis and Candida orthopsilosis : Results from Population-Based Surveillance of Candidemia in Spain

Abstract: We describe the prevalences and susceptibility profiles of two recently described species, Candida metapsilosis and Candida orthopsilosis, related to Candida parapsilosis in candidemia. The prevalences of these species (1.7% for C. metapsilosis and 1.4% for C. orthopsilosis) are significant. Differences observed in their susceptibility profiles could have therapeutic importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
97
3
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 19 publications
19
97
3
9
Order By: Relevance
“…C. metapsilosis isolates displayed a tendency to have diminished susceptibility to FLC, compared with C. parapsilosis sensu stricto with median MICs of 1.5 and 0.5 mg ml 21 , respectively, which are agreement with those observed by van Asbeck et al (1995) and Hensgens et al (2009), showing all isolates to be susceptible to this antifungal compound. Several authors reported sensitivity of C. parapsilosis complex isolates to ITC (Gomez-Lopez et al, 2008;Gonçalves et al, 2010;Kocsubé et al, 2007), which was also noted in our study; this was not the case for one out of four C. metapsilosis isolates, which showed a dose-dependant susceptibility (DDS) to this azole compound, as reported by Gonçalves et al (2010). The majority of the isolates were susceptible to VRC in the present study, which was also found in other studies ( (2008) also observed that higher MICs of CASPO were detected for C. parapsilosis sensu stricto than for C. metapsilosis.…”
Section: Susceptibility Testingsupporting
confidence: 74%
See 3 more Smart Citations
“…C. metapsilosis isolates displayed a tendency to have diminished susceptibility to FLC, compared with C. parapsilosis sensu stricto with median MICs of 1.5 and 0.5 mg ml 21 , respectively, which are agreement with those observed by van Asbeck et al (1995) and Hensgens et al (2009), showing all isolates to be susceptible to this antifungal compound. Several authors reported sensitivity of C. parapsilosis complex isolates to ITC (Gomez-Lopez et al, 2008;Gonçalves et al, 2010;Kocsubé et al, 2007), which was also noted in our study; this was not the case for one out of four C. metapsilosis isolates, which showed a dose-dependant susceptibility (DDS) to this azole compound, as reported by Gonçalves et al (2010). The majority of the isolates were susceptible to VRC in the present study, which was also found in other studies ( (2008) also observed that higher MICs of CASPO were detected for C. parapsilosis sensu stricto than for C. metapsilosis.…”
Section: Susceptibility Testingsupporting
confidence: 74%
“…Sensitivity to AMB was confirmed in previous studies from MICs ¡1 mg ml 21 (Lin et al, 1995;Gomez-Lopez et al, 2008;Gonçalves et al, 2010;Kocsubé et al, 2007). It is of note that Silva et al (2009) reported two cases out of 160 isolates of C. parapsilosis sensu stricto that developed resistance to AMB and Lockhart et al (2008) reported that the MICs of AMB for C. metapsilosis were lower than those of C. parapsilosis sensu stricto.…”
Section: Susceptibility Testingsupporting
confidence: 66%
See 2 more Smart Citations
“…Similarly, FLC resistance in C. metapsilosis and C. parapsilosis sensu stricto has been observed by Chen et al (40) Moreover, Gomez-Lopez et al (41) found an MIC of greater than 4µg/mL FLC for these species, while Silva et al (6) found an MIC of 16µg/mL FLC for one C. parapsilosis sensu stricto isolate. According to Van Asbeck et al (42) , the differences in FLC susceptibility may also refl ect the different affi nities of azoles for the key ergosterol-synthesizing enzyme 14-α-demethylase or for other enzymes in this pathway.…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 95%